Day 3 Wed, October 02, 2013 2013
DOI: 10.2118/166476-ms
|View full text |Cite
|
Sign up to set email alerts
|

Modifying Van Der Waals Equation of State to Consider Influence of Confinement on Phase Behavior

Abstract: Phase behavior and fluid properties in porous media are governed by not only fluid molecule-fluid molecule interactions but also fluid molecule-pore wall interactions. The current available equations of state consider only fluid molecule-fluid molecule interactions and neglect the interactions between the reservoir fluid molecules and the solid wall of the porous media. For conventional reservoirs, this assumption may be valid because the formation pore sizes are much larger than molecular mean free paths. How… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 22 publications
2
25
0
Order By: Relevance
“…These results are in general agreement with the findings from molecular simulation studies of Singh et al (2009). In previous work (Ma et al (2013)), the van der Waals equation of state was modified to model the phase behavior of hydrocarbon fluids for all ranges of pore sizes from bulk (very big pores) to nanopore scale sizes ( In their study, the model provided a priori predictions of the CO 2 adsorption data on the 27 coals with an average absolute percent deviation of 12%. Meanwhile, the generalized SLD-PR model appears to be sufficiently robust and should be extremely useful in reservoir simulators.…”
Section: Introductionsupporting
confidence: 82%
See 1 more Smart Citation
“…These results are in general agreement with the findings from molecular simulation studies of Singh et al (2009). In previous work (Ma et al (2013)), the van der Waals equation of state was modified to model the phase behavior of hydrocarbon fluids for all ranges of pore sizes from bulk (very big pores) to nanopore scale sizes ( In their study, the model provided a priori predictions of the CO 2 adsorption data on the 27 coals with an average absolute percent deviation of 12%. Meanwhile, the generalized SLD-PR model appears to be sufficiently robust and should be extremely useful in reservoir simulators.…”
Section: Introductionsupporting
confidence: 82%
“…• Equation of state Kuz (2002 and2004), Derouane (2007), Travalloni et al (2010a and2010b) and Ma et al (2013)). …”
Section: Introductionmentioning
confidence: 99%
“…These results are in general agreement with the findings from molecular simulation studies of Singh et al (2009). In previous work (Ma et al (2013)), the van der Waals equation of state was modified to model the phase behavior of hydrocarbon fluids for all ranges of pore sizes from bulk (very big pores) to nanopore scale sizes (in shale formations). Such an equation of state can describe the phase behavior and fluid properties of fluids as a function of pore size and molecule size.…”
Section: Introductionsupporting
confidence: 86%
“…In addition, Zarragoicoechea and Kuz (2004) showed that the shifts on the critical temperature are proportional to the size of the mesopore. Normally, as the pore size decreases, the critical temperature and freezing/melting point tend to decrease (Kanda et al 2004;Moore et al 2010).…”
Section: Introductionmentioning
confidence: 99%